EFEKTIFITAS PEMBERIAN TERAPI UAP AIR DENGAN MINYAK KAYU PUTIH TERHADAP POLA NAFAS PADA BALITA DENGAN INFEKSI SALURAN PERNAFASAN AKUT ( I S P A ) DI WILAYAH KERJA PUSKESMAS MUARA ANCALONG: THE EFFECTIVENESS OF GIVING STEAM THERAPY WITH EUCALYPTUS OIL ON BREATHING PATTERNS IN TODDLERSWITH ACUTE RESPIRATORY INFECTION (ARI) AT MUARA ANCALONG HEALTH CENTRE - HAPSA, HAPSA -; Prasetiyarini, Asih (ITKES Wiyata Husada Samarinda, 2025)
Background: Because of the high prevalence of acute respiratory infection in toddlers, steam therapy with eucalyptus oil has not been used as a primary treatment for acute respiratory infection in toddlers at Muara Ancalong Health Center, and there are still many parents of toddlers who choose treatment for their children by providing pharmacological therapy. Purpose: This study aimed to determine the effectiveness of giving steam therapy with eucalyptus oil on breathing patterns in toddlers with ARI. Method: This study used a Pre-Experimental design with One Group pre-post intervention. One Design with a sample of 20 respondents, using a non-random sampling technique with the accidental sampling method. Measuring tools in the form of a checklist sheet and data analysis using the Wilcoxon test. Result: The results of the Wilcoxon test measurement with a significant p-value of 0.000 or < where 0.000 < 0.005, so Ha was accepted, meaning that it showed the effectiveness of giving steam therapy with eucalyptus oil on the breathing pattern of toddlers at Muara Ancalong Health Center in 2021. Conclusion: Giving therapy Non-pharmacological therapy using steam therapy with eucalyptus oil can be used for toddlers who have an acute respiratory infection Keywords: Steam Therapy, Eucalyptus Oil, Breathing Pattern